2018
DOI: 10.1038/s41598-018-22460-0
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the toolbox for cryopreservation of marine and freshwater diatoms

Abstract: Diatoms constitute the most diverse group of microalgae and have long been recognised for their large biotechnological potential. In the wake of growing research interest in new model species and development of commercial applications, there is a pressing need for long-term preservation of diatom strains. While cryopreservation using dimethylsulfoxide (DMSO) as a cryoprotective agent is the preferred method for long-term strain preservation, many diatom species cannot be successfully cryopreserved using DMSO. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 49 publications
0
14
0
1
Order By: Relevance
“…DMSO is a widely used reagent in cell biology. It can dehydrate cells during cryopreservation, thereby preventing the formation of ice crystals in the intracellular environment [32]. Our results showed that compared to the fresh group, the total MPs concentration, the concentration of annexin V-positive MPs, the concentration of BDMPs, the procoagulant function of MPs, the MPs size distribution, and the morphology of the MPs were significantly changed in the DMSO group; however, there was no difference between the DMSO group and the DMSO-free group.…”
Section: Discussionmentioning
confidence: 99%
“…DMSO is a widely used reagent in cell biology. It can dehydrate cells during cryopreservation, thereby preventing the formation of ice crystals in the intracellular environment [32]. Our results showed that compared to the fresh group, the total MPs concentration, the concentration of annexin V-positive MPs, the concentration of BDMPs, the procoagulant function of MPs, the MPs size distribution, and the morphology of the MPs were significantly changed in the DMSO group; however, there was no difference between the DMSO group and the DMSO-free group.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no experiments tested the tolerance of diatoms to low pressure, but we may assume that under such conditions they may suffer from desiccation which is lethal for many diatoms (Souffreau et al 2010(Souffreau et al , 2013a. Similarly, it seems that many diatoms are intolerant to freezing below -40°C, although there are some notable exceptions (Stock et al 2018). In addition to passive dispersal by means of abiotic vectors, biotic vectors might also play a role.…”
Section: Genetic Markermentioning
confidence: 99%
“…This is also what we observed in the three cases with Pinnularia borealis Ehrenberg, H. amphioxys and H. abundans often replacing N. pusilla and Mayamaea spp. The former three taxa are very common, large terrestrial diatoms (±75 µm) and are known to be well-adapted to living in extreme environments (Dodd & Stoermer, 1962;Pipe & Cullimore, 1984;Stock et al, 2018;Van Dam, Mertens & Sinkeldam, 1994). These diatoms are considered to be slow growers, since they spend a large part of their energy in developing complex structures to withstand (very) harsh conditions (Pinseel et al, 2019;Ress, 2012).…”
Section: Habitat Variationmentioning
confidence: 99%